Fever-induced precordial ST-segment elevation in a young man - (:unkn) unknown (My University, 2010)
Brugada syndrome is a rare condition characterized by ST-segment elevation in the right precordial leads. Fever can induce Brugada-like electrocardiographic (ECG) changes. We reported on a 26-year-old male patient with fever and ST-segment elevation in the right precordial leads. Serial cardiac markers were normal and transthoracic echocardiography showed normal wall motion and no evidence for pericardial effusion. Brugada-like ECG changes disappeared after fever resolved. Since the patient had never experienced any arrhythmic symptom, syncope, or spontaneous type 1 ECG, electrophysiological study was not performed and he was not referred for defibrillator implantation. The patient was discharged with strong recommendations to avoid certain medications responsible for Brugada-like ECG changes and to receive urgent treatment for fever. He was asymptomatic during a year follow-up. Emphasis is placed on this particularly rare, but important condition, as it may easily be misdiagnosed and fever may even precipitate ventricular fibrillation.
Keywords: Adult; Humans; Treatment Outcome; Male; Brugada Syndrome; Electrocardiography; Fever; Echocardiography, Transesophageal